Winter Wheat Variety Response to Flag Leaf Foliar Fungicide Application in 2019–2020 - G. Cruppe; B. R. Jaenisch; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2021)
Foliar fungicide can be an important tool in improving wheat yields, but its effectiveness is season- and variety-dependent. To evaluate the yield, test weight, and protein responses of different commercial winter wheat varieties to one foliar fungicide application around heading, we conducted a trial combining four winter wheat varieties and two fungicide management treatments in Manhattan during 2019–2020. The control treatment consisted of no fungicide application, and the alternative treatment consisted of 5 oz/a Absolute Maxx + NIS applied at heading. Varieties evaluated were Bob Dole, Larry, WB4269, and Zenda. The study was conducted under no-tillage practices following a previous soybean crop. Grain yield across varieties averaged 47.8 bushels per acre in the control and 51.3 bu/a in the fungicide treatment. Zenda was the highest yielding variety (51.3 bu/a), followed by Larry (48.9 bu/a), and WB4269 and Bob Dole (~45.5 bu/a). The statistical analysis suggested that all varieties responded similarly to the fungicide application, but we hypothesize that this was because we did not have enough observations to build statistical power. Grain test weight and protein concentration were only impacted by variety and showed no fungicide effect (both were usually greater in Bob Dole and Larry as compared to Zenda or WB4269). These results suggest that the yield increase due to fungicide application did not result in protein dilution, likely due to an extended period for nitrogen (N) uptake and remobilization into the grain. Further research is needed to statistically detect significant differences among varieties in their response to foliar fungicide.
Keywords: wheat; fungicide; variety